2017
DOI: 10.1016/j.jdermsci.2017.02.280
|View full text |Cite
|
Sign up to set email alerts
|

Lowering relative humidity level increases epidermal protein deimination and drives human filaggrin breakdown

Abstract: Background Deimination (also known as citrullination), the conversion of arginine in a protein to citrulline, is catalyzed by a family of enzymes called peptidyl-arginine deiminases (PADs). Three PADs are expressed in the epidermis, one of their targets being filaggrin. Filaggrin plays a central role in atopic dermatitis and is a key protein for the epidermal barrier. It aggregates keratins and is cross-linked to cornified envelopes. Following its deimination, it is totally degraded to release free amino acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 61 publications
(57 reference statements)
5
67
1
1
Order By: Relevance
“…A reduction of ambient humidity and temperature has a negative effect on the skin barrier, and corneocytes cultured in low humidity have been shown to have increased filaggrin degradation . However, in the current study, a 10‐min reduction of skin temperature to 10 °C did not influence epidermal NMF levels at 24 or 48 h. The same applied to intradermal exposure to histamine.…”
Section: Discussioncontrasting
confidence: 60%
“…A reduction of ambient humidity and temperature has a negative effect on the skin barrier, and corneocytes cultured in low humidity have been shown to have increased filaggrin degradation . However, in the current study, a 10‐min reduction of skin temperature to 10 °C did not influence epidermal NMF levels at 24 or 48 h. The same applied to intradermal exposure to histamine.…”
Section: Discussioncontrasting
confidence: 60%
“…In parallel, expression of PAD1 and deimination of proteins including filaggrin in the stratum corneum were enhanced. Treatments of the reconstructed human epidermis by chloro‐amidine, a pan‐PAD inhibitor, partly reversed the effect of dryness on filaggrin degradation . Therefore, we concluded that deimination is necessary and sufficient to upregulate filaggrin degradation in human epidermis when the external humidity level decreases.…”
Section: Normal Function Of Pads In the Epidermal Barriermentioning
confidence: 76%
“…Second, it improves their degradation by bleomycin hydrolase and calpain 1, at least in vitro . Third, it controls the production of NMF amino acids and derivatives according to the external relative humidity . Indeed, in the epidermis of newborn mice, the deimination of proteins, including filaggrin, in the stratum corneum , and the degradation of filaggrin were shown to be strongly upregulated 2 hours after birth .…”
Section: Normal Function Of Pads In the Epidermal Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…The skin modulates the water content of the skin by responding to the level of hydration around it. This is achieved by varying the production of hygroscopic components in the epidermis in relation to humidity conditions . At dryer conditions, degradation of filaggrin proteins is increased to release more hygroscopic free amino acids into the skin.…”
Section: Replicating Properties Of Skinmentioning
confidence: 99%